Assembly Molding for Resistant Media Tight Molded Interconnect Devices - Heinle, Martina; Goth, Christian; Drummer, Dietmar; Franke, Jörg (15th Int. Conference Polymeric Materials, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.assemb

Hot Pin Pull Method - New Test Procedure for the Adhesion Measurement for 3D-MID - Goth, Christian; Kuhn, Thomas; Gion, Gerald; Franke, Jörg (11th International Congress Molded Interconnect Devices, 2014)
The adhesion test of metallic structures on MID (Molded Interconnect Devices) parts is an unsolved issue. So far no method really works reliably. The test methods which are conventionally used are the pull-off test and the shear-test. Both show large standard deviation and the reproducibility is not assured. Nordson DAGE has introduced the new micro-material testing system 4000Plus. This device enables a new test method for the determination of the adhesion strength of MID structures using the hot pin pull (hot bump pull) method. Copper pins (tinned or untinned) are heated up with a user defined temperature profile, soldered to a metallized structure on the MID and then removed vertically upward, while the force is recorded. In this contribution investigations with this new test method are presented.
Keywords: 3D-MID; E|P; Elektronikproduktion; Zuverlässigkeit

Mechatronische Integrationspotenziale durch MID - Goth, Christian; Kuhn, Thomas (Räumliche elektronische Baugruppen (3D-MID), 2013)
Keywords: 3D-MID; E|P

Mediendichte Umhausung spritzgegossener, räumlicher elektronischer Schaltungsträger im Montagespritzguss - Goth, Christian; Heinle, Martina; Franke, Jörg; Drummer, Dietmar (PLUS - Produktion von Leiterplatten und Systemen, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.medien

Räumlich und mit feiner Struktur: Die 3D-Technologie auf dem Vormarsch - Goth, Christian; Kuhn, Thomas (Kunststoffe, 2015)
Molded Interconnected Devices (MID) sind dreidimensionale elektronische Baugruppen. Ihre Stärken liegen in der hohen Gestaltungsfreiheit, dem erreichbaren Miniaturisierungsgrad und der damit einhergehenden Gewichtsreduktion sowie in der Integration einer Vielzahl von Funktionalitäten. Diese mechatronischen Systeme werden in verschiedensten Anwendungsfeldern wie Automobil, Industrieelektronik, Medizintechnik, Telekommunikation und Sensorik eingesetzt. Interessante 3D-MID (spritzgegossene Schaltungsträger)-Komponenten beleuchtet der nachfolgende Beitrag. Er zeigt die Trends der genannten Anwendungsfelder, die sich in hohem Maße auf die Entwicklung der Prozesse, der Anlagentechnik und vor allem der Werkstoffe für die 3D-MID-Technologie auswirken. Hierzu zählen der zunehmende Bedarf an feineren Leiterbahn-Strukturen, die deutlich unter dem bisherigen Standard von 150 extgreekmm liegen, die notwendige Wärmeverteilung insbesondere für LED-Applikationen, eine hohe Zuverlässigkeit trotz steigender Umweltanforderungen und kostengünstige Systemlösungen vergleichbar mit konventionellen Technologien (z. B. starre und flexible Leiterplatte). Die Werkstoffentwicklung zielt demzufolge auf die Realisierung feinerer Füllstoffpartikel, wärmeleitfähiger Materialien bzw. Systeme und die Qualifizierung alternativer Hochleistungstypen als technologisch und wirtschaftlich interessante Alternativen zu dem bewährten LCP (Liquid Crystal Polymer oder Flüssigkristallpolymer)-Typ Vectra E840i LDS der Celanese GmbH, Sulzbach. Ergänzend zu den thermoplastischen Materialen werden auch neue Entwicklungen im Bereich der spritzgießfähigen Duroplaste betrachtet.
Keywords: E|P; MID

Three-Dimensional and with a Fine Structure: 3-D Technology on the Rise - Goth, Christian; Kuhn, Thomas (Kunststoffe International, 2015)
Molded Interconnected Devices (MID) are three-dimensional electronic assemblies (3-D). Their strengths lie in the great freedom of design, the degree of miniaturization attainable and the resultant weight reduction as well as in integration of numerous functions. These mechatronic systems are used in a wide variety of applications such as automotive, industrial electronics, medical devices, telecommunications and sensor technology. The following article highlights a number of interesting 3-D MID (injection molded circuit carriers) components. It discusses the trends in the fields of application mentioned that have a significant effect on the development of the processes, the equipment technology and, above all, the materials for 3-D MID technology. These include the growing demand for finer circuit trace structures that are considerably below the current standard of 150 µm, the necessary heat distribution for LED applications in particular, a high reliability despite increasingly stringent environmental regulations and cost-effective system solutions comparable to conventional technologies (e.g. rigid and flexible circuit boards). Accordingly, materials development is focusing on the production of finer filler particles, heat-conducting materials or systems and qualification of alternative high-performance grades as technologically and economically interesting alternatives to the proven LCP (Liquid Crystal Polymer) grade Vectra E840i LDS from Celanese GmbH, Sulzbach, Germany. Besides thermoplastic materials, new developments in the field of injection moldable thermosets are being evaluated.
Keywords: E|P; MID